Documenting adaptations across the Accelerating Colorectal Cancer Screening and follow-up through Implementation Science research programs: methods and adaptation examples - Rabin, Borsika A.; Kenzie, Erin S.; Oliveri, Jill M.; Kruse-Diehr, Aaron J.; Hoover, Sonja; Menon, Usha; Doescher, Mark P.; Adsul, Prajakta; Mishra, Shiraz I.; English, Kevin; Nodora, Jesse; Lam, Helen; et al. (Frontiers in Health Services, 2025)
IntroductionAdaptations are common, expected, and often imperative for successful uptake and sustained implementation of clinical or public health programs in real-world practice settings. Understanding which adaptations have been made to evidence-based interventions and subsequent implementation strategies throughout the life cycle of a project can contextualize findings and support future scale-up of the program. Systematic documentation of adaptations is rarely conducted or reported, and little guidance exists on approaches to documenting adaptations.MethodsAccelerating Colorectal Cancer Screening and follow-up through Implementation Science (ACCSIS) is a National Cancer Institute-funded Beau Biden Cancer MoonshotSM Initiative developed to improve colorectal cancer screening, follow-up, and referral for care among underserved groups, including diverse racial and ethnic populations and people living in rural areas. Using an iterative data gathering approach—a survey, data abstraction, and data validation—we compiled information about adaptation documentation and analytic methods and intervention and implementation strategy adaptations from the eight funded ACCSIS research programs. An analytic team representing multiple ACCSIS programs reviewed, coded, and summarized the data using a rapid qualitative analytic approach.ResultsACCSIS programs varied substantially in how they defined and documented adaptations. Nine approaches were used to document adaptations; the most common were periodic reflections and review of meeting minutes and agendas. Nine analytic methods were reported to guide adaptation analysis; the most frequently mentioned were rapid qualitative methods, descriptive statistics, and mixed-methods analysis. A total of 96 adaptations were reported by the eight research programs, most of which occurred during the pre-implementation stage (68%) or were made to the program format (71%). Only 36% of the adaptations were due to the COVID-19 pandemic.ConclusionsOur multi-method, systematic approach allowed us to explore how sites document and analyze adaptations across eight ACCSIS Moonshot programs. Using a systematic approach allowed for comparisons of intervention and strategy adaptations within and across research programs and can inform the science of adaptations, while building a knowledge base of why such adaptations are needed and how they can inform implementation efforts across time. Methods described herein provide a template for similar assessment activities in other large, multi-site research initiatives.